Pattern of blindness in a community based hospital of Nepal - Sharma, R; Marasini, S; Nepal, BP (Nepalese Journal of Ophthalmology, 2013)
Introduction: Because of the availability of modern health facilities and moderately easy access to health services in the last 25 years, the blindness due to cataract and trachoma is expected to decline in Nepal. So it is felt that the causes of blindness need to be revised. Objective: To regroup the disease pattern leading to permanent blindness in patients attending a suburban multidisciplinary community-based hospital of Nepal. Materials and methods: A cross-sectional, descriptive study was conducted in patients attending Dhulikhel hospital over a period of 12 months, from March 2010. Only the patients with best corrected visual acuity of < 3/60 were enrolled in the study. A detailed ocular examination was carried out. Results: A total of 76 eyes of 58 patients were analyzed. Of all, 32 were male (55.2 %). The mean age of the patients was 43.03 ± 22.98, with a range of 7 years to 84 years. Retinal diseases had the higher prevalence (23, 39.7 %) followed by amblyopia (10, 17.2 %) and corneal diseases (9, 15.51 %). Anisometropic amblyopia (3.94 %) was the commonest type of amblyopia. Retinitis pigmentosa (9.21 %) and age-related macular degeneration (7.89 %) were common retinal diseases whereas anterior staphyloma (5.26 %) and leucoma (3.94 %) were common corneal diseases. Other important and rare causes of blindness included ethambutol-induced optic neuropathy and vitelliform dystrophy. Conclusion: Periodic collection of statistics on the relative frequency of the causes of blindness is important in socioeconomically developing nations like Nepal. This helps to revise the pattern of blinding diseases so that priorities can be redefined. Nepal J Ophthalmol 2013; 5(9):50-56 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7822